Hubungan Antara Dukungan Sosial dan Konsep Diri dengan Kecemasan Sosial pada Narapidana di Rutan Kelas IIB Kudus - Izzatun Nabilah; Mohammad Khasan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Social anxiety is excessive fear or worry about situations that make a person feel anxious in social situations because of negative assessments from other people. Prisoners are convicts who are fostered in prison after being sentenced. The purpose of this research is to determine the relationship between social support and self-concept and anxiety. social relations among prisoners. The sampling in this study used a purposive sampling technique with 50 prisoners as subjects. Based on the results of the SPSS analysis, it shows that the hypothesis tested in the study was rejected with a significance of 0.520 (p>0.05), which means it is greater than 0.05. It can be concluded that there is no relationship between social support and self-concept and social anxiery im prisoners at the Class IIB Kudus Detention Center.